2022
DOI: 10.1097/ta.0000000000003767
|View full text |Cite
|
Sign up to set email alerts
|

The effects of timing of prehospital tranexamic acid on outcomes after traumatic brain injury: Subanalysis of a randomized controlled trial

Abstract: In this study we examine the effect of early versus delayed prehospital administration of tranexamic acid in patients with traumatic brain injury. Outcomes were not significantly different but select complications were lower with early administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Measurements were selected based on the literature review and the study purpose [5,13, 16]. Baseline characteristics included age, gender, body mass index (BMI); medical parameters at admission included hypertension history, diabetes history, Glasgow Coma Scale (GCS) score, heart rate, systolic blood pressure (SBP), and Spo2; time of TXA administration since head injury (TXAT, the injury time regarded as the time call for an emergency service dispatch), the mannitol and TXA administration interval (Time interval between the nurse's signature on the two medical orders).…”
Section: Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements were selected based on the literature review and the study purpose [5,13, 16]. Baseline characteristics included age, gender, body mass index (BMI); medical parameters at admission included hypertension history, diabetes history, Glasgow Coma Scale (GCS) score, heart rate, systolic blood pressure (SBP), and Spo2; time of TXA administration since head injury (TXAT, the injury time regarded as the time call for an emergency service dispatch), the mannitol and TXA administration interval (Time interval between the nurse's signature on the two medical orders).…”
Section: Measurementmentioning
confidence: 99%
“…This is the most signi cant medical and teaching hospital in North Sichuan Province, China, a certi cated province-level regional medical center and national trauma center, with more than 2000 referrals annually. Included criteria: (1) aged between 18 to 80 years, (2) diagnosed as TBI and recon rmed ICH by computer tomography, (3) de ned with a 3 ≤ Glasgow Coma Scale (GCS) score ≤ 12 at admission, (4) have received 2g TXA [13] and 50g mannitol during prehospital treatment, (5) TXA treatment administrated within two hours since the head injury [13], ( 6) at least have one pupil reaction. Excluded criteria: (1) have other intrinsic VTE risks mentioned by the Caprini score [14], (2) work or live at an altitude of more than 3,500 meters [15], (3) take warfarin or antiplatelet agent within one month, (4) received other hemostatic or dehydration agent during prehospital treatment, (5) died before hospitalized (6) systolic blood pressure < 90 mmHg at admission (7) Incomplete data.…”
mentioning
confidence: 99%
“…In a mouse model of TBI, Wallen et al (177) demonstrated that TXA is neuroprotective but leads to a SIRS response with serum cytokine elevation. Both the CRASH-3 trial (172) and the Prehospital TXA for TBI Trial (175,178) had nonsignificant primary outcomes of TXA versus placebo. However, these studies demonstrated the safety of TXA in TBI patients.…”
Section: Tranexamic Acidmentioning
confidence: 99%
“…TXA administration in the prehospital environment has been extensively investigated in recent years. 31,32 Several large, highquality studies have failed to support benefit for most braininjured patients, leading to a strong recommendation against routine use in these guidelines. The Brain Injury: Prehospital Registry of Outcome, Treatments and Epidemiology of Cerebral Trauma study was a large prospective observational study of 1827 patients which reported increased mortality in patients treated with TXA (odds ratio 1.34, P < .001).…”
Section: Tranexamic Acidmentioning
confidence: 99%